(−3)3(−3)2(−3)−5(−3)5⋅84=?
First, let's recall the law of exponents for multiplication between terms with identical bases:
am⋅an=am+n
We'll use this to deal with the fraction's denominator in the problem:
(−3)3(−3)2(−3)−5(−3)5⋅84=(−3)3+2+(−5)(−3)5⋅84=(−3)0(−3)5⋅84
In the first stage, we'll apply the above law to the denominator and then simplify the expression with the exponent in the denominator.
Now let's remember that raising any number to the power of 0 gives the result 1, or mathematically:
X0=1
Therefore the denominator that we get in the last stage is 1.
This means that:
(−3)3(−3)2(−3)−5(−3)5⋅84=(−3)0(−3)5⋅84=1(−3)5⋅84=(−3)5⋅84
Now let's recall the law of exponents for an exponent of a product in parentheses:
(x⋅y)n=xn⋅yn
We'll apply this law to the first term in the product:
(−3)5⋅84=(−1⋅3)5⋅84=(−1)5⋅35⋅84=−1⋅35⋅84=−35⋅84
Note that the exponent applies separately to both the number 3 and its sign, which is the minus sign that is actually multiplication by −1.
Let's summarize everything we did:
(−3)3(−3)2(−3)−5(−3)5⋅84=(−3)5⋅84=−35⋅84
Therefore the correct answer is answer C.
−35⋅84